Little Bo in Italy the continued adventures of Bonnie Boadicea - Andrews, Julie 1935- (HarperCollins Children's Books, 2010)
The little cat called Bonnie Boadicea and her new owner find great adventure while traveling along the coast of Italy, where Bo continues to seek her missing sister and joins the circus--at least for a while